G-convergence of parabolic operators and weak convergence of solutions of diffusion equations - Makhno, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The relationship between the G-convergence of parabolic operators and the weak convergence of solutions of diffusion equations is established. Constructive conditions are obtained for determining coefficients of a G-limiting operator.